NEW METHODS OF PEDAGOGICAL TECHNOLOGIES USED IN FOREIGN LANGUAGE TEACHING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses some theoretical analysis of using pedagogical technologies in foreign language teaching. Moreover, it gives brief explanation on effective methods and their peculiarities.